Constitutive expression of high affinity interleukin 2 receptors on human CD16-natural killer cells in vivo. - Arnon Nagler; Lewis L. Lanier; J H Phillips (1990)
The majority of human NK cells express low affinity IgG Fc receptors (CD16+), whereas a minor subset of NK cells lack Fc receptor expression (CD16-). In contrast to CD16+ NK cells that express only p75 IL-2 receptors, CD16- NK cells constitutively co-express both p75 and p55 IL-2 receptors in vivo and preferentially respond to low concentrations of IL-2 with increased cytolytic activation and proliferation. Scatchard analysis demonstrated the presence of approximately 1,200 high affinity (approximately 25 pM kD) and approximately 9,600 intermediate affinity (approximately 2 nM kD) IL-2 receptors on CD16- NK cells. CD16+ NK cells expressed only a single intermediate affinity IL-2 receptor of approximately 1.9 nM kD (approximately 9,000 sites per cell). The IL-2 binding data thus substantiated the phenotypic and functional studies and definitively show that the differential responsiveness of CD16- and CD16+ NK cells to IL-2 is manifested through different affinity IL-2 receptors.